2007
DOI: 10.1890/05-1106
|View full text |Cite
|
Sign up to set email alerts
|

Land Change in the Southern Yucatán and Calakmul Biosphere Reserve: Effects on Habitat and Biodiversity

Abstract: The southern Yucatán contains the largest expanse of seasonal tropical forests remaining in Mexico, forming an ecocline between the drier north of the peninsula and the humid Petén, Guatemala. The Calakmul Biosphere Reserve resides in the center of this region as part of the Mesoamerican Biological Corridor. The reserve's functions are examined in regard to land changes throughout the region, generated over the last 40 years by increasing settlement and the expansion and intensification of agriculture. These c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
97
1
17

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 112 publications
(119 citation statements)
references
References 39 publications
2
97
1
17
Order By: Relevance
“…Furthermore, clearing mature forest is unlikely because current policies promote cultivation on extant open land or secondary forest. We have not observed either an increase in fallow length or an increase in deforestation of previously uncut forest (42). Adding fertilizer P is not economically viable at present but could be in the future.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Furthermore, clearing mature forest is unlikely because current policies promote cultivation on extant open land or secondary forest. We have not observed either an increase in fallow length or an increase in deforestation of previously uncut forest (42). Adding fertilizer P is not economically viable at present but could be in the future.…”
Section: Discussioncontrasting
confidence: 59%
“…We also sampled bulk deposition of P at an open field. Previous work in ER has shown that forests such as these would be 5.7, 9.3, and 12.1 m tall, with a density of 70, 550, and 880 trees per hectare Ͼ10 cm diameter at breast height, respectively (42). In each stand, fourteen 10-liter plastic buckets were dispersed every 3 m along three 15-m-long transects.…”
Section: Methodsmentioning
confidence: 99%
“…Unless interrupted by specific disturbances such as fire-friendly plant invasion or management practices, post-fire vegetation grows back at a rapid rate after a burn. In much of the Yucatán Peninsula, secondary vegetation can reach a height of 10 m within-five years of clearing [36][37][38]. As a consequence, there is typically only a short window of time to detect land change.…”
Section: Study Areamentioning
confidence: 99%
“…No se cuenta con información suficiente sobre H. calakmulense y el estado de conservación de sus poblaciones, al ser reconocida como nueva especie hace poco tiempo. Las principales amenazas a que se han enfrentado estas especies están relacionadas con las diferentes actividades antropogénicas que se han desarrollado en sus hábitats (Rico y García, 1991;Escalante y Aroche, 2000), las cuales se mantienen en la actualidad (Roy y Turner II, 2006;Vester et al, 2007).…”
Section: Introductionunclassified